“Your Letters are as Cordial as a Friend’s Handshake” (Correspondence between André Gide and Fyodor Rosenberg) - Kirill A. Chekalov (Studia Litterarum, 2022)
St. Petersburg branch of the Archive of the Russian Academy of Sciences stores a correspondence between a famous French writer André Gide and a renowned soviet Orientalist scholar, member of the USSR Academy of Sciences, Fyodor Rosenberg (1867–1934). Part of the correspondence is kept in the Parisian library Jacques Doucet. In 1921, the University of Lyon published the epistolary in French (in total 338 letters). The correspondence covers a long period from 1896 to the date of death of the Russian academic. This letters allow to contemplate the spiritual world of two outstanding cultural figures of the fin de siècle, as well as to see once again how the revolution in Russia influenced the mindset and the way of life of academic life. The fact that the epistolary lacks a number of letters is mainly explained by the 1917 Revolution. Only a short collection of letters dates back to the 1920s (when Rosenberg was a senior research curator at the Asiatic Museum, now the Institute of Oriental Manuscripts of the Russian Academy of Sciences), while the early 20th century is broadly represented in the correspondence. Social and political reality becomes more and more catastrophic as it invades that highly estheticized, sometimes explicitly Pre-Raphaelite-like universe into which Rosenberg, a refined expert in both Eastern and Western-European cultural traditions, would like to withdraw. “Beautiful Italy” occupies a significant place in the letters. Rosenberg’s deep emotions connected with his being a homosexual are also an important part of the epistolary. The edition is prepared by Nikol Dziub, professor at the University of Upper Alsace (UHA). The introductory note and an extensive pageby- page commentary provide a comprehensive view of the reality, cultural landmarks, and personalities that appear in the correspondence.